2020
DOI: 10.3389/fncel.2019.00587
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Channelopathies in Genetic and Acquired Epilepsies

Abstract: Epilepsy is a common neurological disorder characterized by recurrent uncontrolled seizures and has an idiopathic "genetic" etiology or a symptomatic "acquired" component. Genetic studies have revealed that many epilepsy susceptibility genes encode ion channels, including voltage-gated sodium, potassium and calcium channels. The high prevalence of ion channels in epilepsy pathogenesis led to the causative concept of "ion channelopathies," which can be elicited by specific mutations in the coding or promoter re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 147 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…[2]. There is an increased understanding of the contribution of neuroinflammation, channelopathies, neurodegeneration, neurogenesis, neural reorganization, and plasticity in epilepsy [10,11]. In recent years, several findings have repeatedly reinforced the role of neuroinflammation in epilepsy [7,12,13], indicating that targeting brain inflammation might be a possible therapeutic strategy against epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2]. There is an increased understanding of the contribution of neuroinflammation, channelopathies, neurodegeneration, neurogenesis, neural reorganization, and plasticity in epilepsy [10,11]. In recent years, several findings have repeatedly reinforced the role of neuroinflammation in epilepsy [7,12,13], indicating that targeting brain inflammation might be a possible therapeutic strategy against epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy also exhibits idiopathic "genetic" etiology or symptomatic "acquired" elements. Several susceptibility genes encoding ion channels, including voltage-gated sodium, potassium, and calcium channels, have been unraveled from genetic investigations [11]. Mutations in three alpha subunit genes (SCN1A, SCN2A, SCN8A) of the voltage-gated sodium channels (VGSCs) have been implicated in epilepsy [16].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of TFs is one of the earliest responses following a brain insult 36 . Recently, we have identified several key transcriptional control mechanisms of CA1 pyramidal burst firing activity, namely transcriptional activation by the transcription factors Metal Regulatory Transcription Factor 1 (Mtf1) and Early Growth Response 1 (Egr1) 7 , 37 .…”
Section: Resultsmentioning
confidence: 99%
“…a) Vertex aberrance: Most prior work in epilepsy conceived aberrance to arise from a seizure focus, which can be regarded as a vertex (or a group of vertices). These prior studies reported abnormalities in cell dynamics caused by channelopathies (van Loo and Becker, 2020), or changes in the structure of a brain region, such as a focal cortical dysplasia (Gill et al, 2021;Sinha and Davis, 2021) or hippocampal sclerosis (Winston et al, 2013;Chen et al, 2018). b) Edge aberrance: Altered connections between neurons or areas can be caused by changes in conduction velocities, which could occur due to changes in myelination, or by changes in synaptic dynamics.…”
Section: Vertex and Edge Aberrancementioning
confidence: 99%